Determinantes socioeconómicos y demográficos del crimen en Chile - Nuñez, Javier; Rivera, Jorge; Villavicencio, Xavier; Molina, Oscar (Estudios de Economía, 2016)
This paper is a first attempt at analyzing the determinants of crime in Chile. We employ a static panel for the thirteen regions of Chile from 1988 to 2000. Following the standard Becker-Ehrlich model, the empirical model includes various variables linked to incentives to commit crimes, such as legal and illegal income (from labor and crime, respectively), legal income opportunities (captured by regional unemployment) and a measure of regional police efficiency, measured as the ratio of crime reports and captures. In addition, we include demographic and socioeconomic variables that may also explain the evolution and dispersion of crime, namely the gender, age and urban-rural composition of the population, human capital variables (schooling and literacy), and various relative and absolute poverty measures. The main conclusion is that the incentive-related variables explain an important part of the variation of economically-motivated crimes; Robbery, Drugs and Fraud. However, except for the unemployment rate, these variables do not explain the variation of other, largely non economically-motivated crimes, namely Rapes, Murder and Manslaughter, and Physical aggression. Finally, while the gender, age and urban-rural composition of the population explain part of the variation of crime, we find that human capital and poverty measures do not offer robust and conclusive results, which confirms what has been consistently reported in the empirical literature.